Studi Evaluatif Pemanfaatan Alat Peraga Tradisional dalam Pembelajaran Pendidikan Jasmani di Sekolah Dasar - M. Asri B (Lembaga Yasin AlSys, 2026)
Although the use of instructional aids in Physical Education has been widely discussed, studies that specifically evaluate the effectiveness of traditional, local-wisdom–based instructional aids in enhancing elementary students’ participation and motor skills remain limited, particularly in Barru Regency. This study aimed to evaluate the effectiveness of traditional instructional aids in Physical Education learning at SDN 144 Barru Regency, conducted from November to December 2025. A mixed-methods approach with a descriptive evaluative design was employed, involving 42 participants comprising 2 Physical Education teachers and 40 fourth- and fifth-grade students selected through purposive sampling. Data were collected through observation, questionnaires, interviews, and motor skills tests; quantitative data were analyzed using paired-samples t-tests, while qualitative data were analyzed using thematic analysis. The results showed a significant improvement in students’ motor skills after the use of traditional instructional aids (t = 5.87; p < 0.001) and an increase in the mean participation score from 68.45 to 82.30, with a significance value of 0.000 (p < 0.05). In addition, questionnaire results indicated a 21% increase in learning motivation compared to pre-intervention levels. Qualitative findings reinforced the quantitative results, revealing greater enthusiasm, active engagement, and improved collaboration among students during instruction. The study concludes that traditional instructional aids are effective in improving the quality of Physical Education learning and implies that schools and teachers should optimize local-wisdom–based innovations as a contextual, economical, and sustainable instructional strategy.